Hydrophyte communities in the Tam Giang - Cau Hai lagoon - Luong, Cao Van; Tien, Dam Duc; Nga, Nguyen Thi (Vietnam Journal of Marine Science and Technology, 2020)
The Tam Giang - Cau Hai lagoon in Thua Thien-Hue province is the largest lagoon in South East Asia and also one of the places having the largest area of seagrass in Vietnam. The study results from 2009 to 2017 showed that 6 seagrasses species were identified (Halodule uninervis is a newly recorded species, however, Halophila minor is not recorded) and there were 8 freshwater grass species (with the exception of Potamogeton maackianus), with a total area of 2,840 ha. In particular, the area of seagrass has been recovering significantly from 1,000 hectares in 2009 to 2,037 hectares in 2017.